Design, Synthesis, Computational Insights and Systems Biology-based Investigation of {[(quinoxalin-2-yl)amino]phenyl}pyrimidine derivatives as Anti-breast Cancer agents (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Heterocyclic compounds play a vital role in the treatment of various ailments. Network pharmacology is an emerging technique for investigating the molecular effects of compounds. In this current research, novel quinoxaline-mediated pyrimidine derivatives were designed, synthesized and evaluated for their potential using the network pharmacology approach. The compounds were synthesized under microwave irradiation and characterized using FTIR, NMR and HRMS spectral studies, confirmed the structural integrity. The mechanistic pathway and the prominent targets were identified using network pharmacology and enrichment analyzes. These analyzes merely showed that the designed compounds would be highly active against breast cancer by targeting the Estrogen signalling pathway. The gene survival analysis exhibited that the targets (ESR1 and ERBB2) were significant. The physicochemical, pharmacokinetic and toxicity parameters of the designed compounds were evaluated and the findings of these studies showed the druggable nature of the compounds. The drug score in the range of 0.3-0.6 was observed, calculated using the OSIRIS Molecular Property Explorer. Molecular docking using the Schrödinger Suite was performed against the selected targets and compared with the co-crystallized ligands and standards. Among them, derivative F17 was found to be highly active with binding energies of -9.04 Kcal/Mol and -11.52 Kcal/Mol against ESR1 and ERBB2, respectively. The binding interactions of this compound found to be superimposable with the co-crystallized ligand, which will be suitable for molecular dynamics simulations. The anticancer activity was also predicted using the in-mac lab software and compared for its efficiency. The graph theoretical studies at the DFT level for the lead-like molecules confirmed the stability and potency of the compounds. Thus, these derivatives can be effectively used in the management of breast cancer. However, biological studies are warranted.
Keywords: Quinoxaline; Pyrimidine; Spectral studies; Network Pharmacology; DFT; Computational studies